Superação de dormência e estabelecimento de plântulas normais e anormais para produção de mudas de Ochroma pyramidale (Cav. ex Lam.) Urb - Bao, Francielli [UNESP]; Da Rocha, Maíra; De Oliveira, Maiby Teodoro; Bambil, Deborah; Luz, Petterson Baptista (My University, 2016)
Ochroma pyramidale (Cav. ex Lam.) Urb has great economic importance due to fast growth have, tegument dormancy, and variation in the germination process, where dormancy overcoming is fundamental in the study of seedlings. The aim of this study was to describe the external morphology of early stage development and test pre-germination treatments with hot water and sulfuric acid, under presence and absence of light, at different temperatures, as well, as to assess the establishment of normal and abnormal seedlings. For this there were five methods of scarification, three conditions of temperatures associated with two light regimes, and in nursery; the establishment of normal and abnormal seedlings was evaluated. Germination was classified as epigeal phanerocotylar, the treatment with immersion in water 80°C and H2SO4 120 was the most suitable to overcome dormancy, the optimal temperature was 30°C. Normal and abnormal seedlings have high capabilities of establishment.
Overcoming dormancy and establishment of normal and abnormal seedlings for seedling production of Ochroma pyramidale (Cav. ex Lam.) Urb
Keywords: Forest species; Germination; Tegument impermeability